Spatial Analysis Of Development Yogyakarta City 1925-2020 In Disaster Risk Perspective - Astuti, Nurul Indri; Sutisna, Sobar; Subiyanto, Adi; Widodo, Pujo; Wilopo, Wilopo (PendIPA Journal of Science Education, 2024)
A city will experience development over time because of growth population, economic, social, and culture activities, also interaction between cities. Yogyakarta also has undergone changes and developments that can be seen from road network, settlements, and green open spaces. This research aimed to study changes of Yogyakarta city from 1925-2020 based on road network, settlements, and green open spaces. Study used Yogyakarta’s old map from 1925, 1933, and 1946, map of Indonesia’s topography 2000, and RTRW 2020 maps. Analysis was done using overlay technique that result in changes from road network, settlements, and green open spaces also spatial structure that occurred during that period with GIS software. The result showed that Yogyakarta development was influence by the distribution of road network and existence of community activities centers. Spatial structure of Yogyakarta has not shown significant changes, it is still in the form of monocentric city with multi-nodal category. The development of this city shows that Yogyakarta already has a disaster-safe city planning.